Measuring the Success Agency for Drug and Food Control Republic of Indonesia Facilitators as Food Safety Extension Workers in Simalungun, Karo, Serdang Bedagai and Samosir District In 2019 - Rona Monika Sihaloho; Ella Nurlaela Hadi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The agency for drug and food control republic of Indonesia in synergy with the academic community of Health Polytechnic in Medan implemented a food safety extension facilitator programme to protect the public from unqualified food. The study aims to measure the success of the facilitators in educating food business operators in Simalungun, Karo, Serdang Bedagai and Samosir districts on food safety. The research data were taken from the report on the results of activities as a facilitator of the agency for drug and food control republic of Indonesia in 2019, on behalf of the health polytechnic students in Medan. Counseling was conducted through presentations and discussions in the village hall or in the facilities of the participants, depending on the availability of facilities in each village. Prior to the presentation, a pre-test questionnaire was completed to measure the knowledge of participants, after which the material was presented and discussed. A post-test questionnaire was then completed to measure the participants' level of knowledge. The total number of participants from 5 districts was 268 people. Using the SPSS method of the Wilcoxon Matched-Pairs statistical test, the significance value (p-value) of the pre-test and post-test data was found to be 0.005 (<0.05). The face-to-face counselling methods or presentations followed by discussions were shown to increase participants' knowledge as measured by the pre-test and post-test scores. Thus, the food safety extension facilitator programme can improve participants' knowledge, is an intervention that can be continued throughout Indonesia by involving related sectors to achieve safe, quality and efficacious or beneficial food products based on the Small and Medium Enterprises (MSMEs) food.Keyword: Agency for Drug and Food Control, facilitator, food safety, counseling, MSMEs